Plant Communities Rather than Soil Properties Structure Arbuscular Mycorrhizal Fungal Communities along Primary Succession on a Mine Spoil - Krüger, Claudia; Kohout, Petr; Janoušková, Martina; Püschel, David; Frouz, Jan; Rydlová, Jana (Frontiers in Microbiology, 2017)
Arbuscular mycorrhizal fungal (AMF) community assembly during primary succession has so far received little attention. It remains therefore unclear, which of the factors, driving AMF community composition, are important during ecosystem development. We addressed this question on a large spoil heap, which provides a mosaic of sites in different successional stages under different managements. We selected 24 sites of c. 12, 20, 30 or 50 years in age, including sites with spontaneously developing vegetation and sites reclaimed by alder plantations. On each site, we sampled twice a year roots of the perennial rhizomatous grass Calamagrostis epigejos (Poaceae) to determine AMF root colonization and diversity (using 454-sequencing), determined the soil chemical properties and composition of plant communities. AMF taxa richness was unaffected by site age, but AMF composition variation increased along the chronosequences. AMF communities were unaffected by soil chemistry, but related to the composition of neighboring plant communities of the sampled C. epigejos plants. In contrast, the plant communities of the sites were more distinctively structured than the AMF communities along the four successional stages. We conclude that AMF and plant community successions respond to different factors. AMF communities seem to be influenced by biotic rather than by abiotic factors and to diverge with successional age.